UNUSUAL PRESENTATION OF SOLITARY BONE CYST - A CASE REPORT - Ajila, Vidya; R., Gopakumar; Hegde, Shruthi; Babu, Subhas; K., Harini (Journal of Health and Allied Sciences NU, 2014)
Solitary bone cyst, also known as traumatic bone cyst or idiopathic bone cyst, is a bony cavity with no epithelial lining and no infection, containing fluid and small amounts of tissue. Clinically these lesions are usually asymptomatic and detected accidentally on routine radiographic examination. Normally, they are empty cavities sometimes having a thin lining of connective tissue without epithelium. They may contain serosanguinous fluid, clots, erythrocytes, fibrin and giant cells. In this report, we present a case of solitary bone cyst in the anterior mandible which was associated with pain.
Keywords: Solitary bone cyst; Traumatic bone cyst; bone cavity